Gemcitabine plus pegylated liposomal doxorubicin in patients with advanced epithelial ovarian cancer resistant/refractory to platinum and/or taxanes. A HeCOG phase II study - Skarlos, D.V.; Kalofonos, H.P.; Fountzilas, G.; Dimopoulos, M.A.; N. Pavlidis; Razis, E.; Economopoulos, T.; Pectasides, D.; Gogas, H.; Kosmidis, P.; Bafaloukos, D.; Klouvas, G.; et al. (Anticancer Research, 2005)
Background: A phase II study was conducted to evaluate the efficacy and toxicity of the combination of gemcitabine (GEM) and pegylated liposomal doxorubicin (PLD) in patients with platinum- and/or taxane-resistant/refractory advanced epithelial ovarian cancer (AEOC). Patients and Methods: Patients (pts), who had been treated with platinum or paclitaxel and met the criteria of resistant/refractory AEOC, received GEM 650 mg/m2 days 1 and 8 and PLD 25 mg/m2 day 1 every 4 weeks up to a total of 6 cycles, unless disease progression or adverse effects prohibited further therapy. Results: Thirty-seven patients entered the study. There was 1 complete (3%) and 7 partial responses (19%) for an overall response rate of 22%. Two patients had stable disease (5.5%). After a median follow-up of 16.2 months, the median survival was 8.4 months and time to treatment failure 2.7 months. The most frequent severe toxicity was myelosuppression recorded in 13 (35%) patients. Severe stomatitis was recorded in only 2 (5%) cases and severe palmar-plantar erythrodysesthesia in 1 patient. One severe allergic reaction (grade 4) to PLD was recorded following the third cycle of treatment. Conclusion: The combination of GEM and PLD in patients with AEOC, who are resistant/refractory to platinum and/or Taxanes, did not show any superiority over monotherapy. However, in view of the acceptable toxicity profile, the above combination may deserve further investigation in a randomised setting.
Keywords: Gemcitabine; Ovarian cancer; Pegylated liposomal doxorubicin